Some Transition Metal Complexes with 2-thioacetic acid-5-pyridyl-1,3,4-oxadiazol - Najeeb, Dina A (Al-Nahrain Journal of Science, 2018)
New metal complexes of the ligand 2-thioaceticacid-5-Pyridyl-1,3,4-oxadiazole (HL) with the metal ions Ni (II) Cu(II) Co (II) and Fe (III) were prepared in alcoholic medium, the prepared complexes were characterized by FTIR spectroscopy, electronic spectroscopy, elemental analysis, magnetic susceptibility, conductivity measurements and CHNO and S analysis. From the Spectral measurements, monomer and octahedral structures for the complexes were proposed.